Surveillance Method for Surgical Site Infection - Goyal, Rochak; Singh Sandhu, Harinder Pal; Kumar, Ashwani; Kosey, Sourabh; Mehra, Neelesh (Indian Journal of Pharmacy Practice)
Surgical Site Infection (SSI) is the third most commonly reported Nosocomial infection and accounts for 14–16% of all Nosocomial infections among hospital inpatients. The morbidity, mortality and the cost to health services of surgical site infections is huge. In addition, many workers have shown that feedback of appropriate data to surgeons has been an indispensable component of strategies to reduce SSI rates. The elements essential for a successful programmed of prevention of SSIs include intensive surveillance, infection control activities and regular feedback of SSI rates to surgeons. Surveillance with information feedback to surgeons and other medical staff has been shown to be an important element in the overall strategy to reduce the numbers of SSIs. Despite the apparent effectiveness in lowering SSI rates when surgeons receive feedback, however, there has been no consensus on which surveillance methods are best for collecting data on SSIs. A successful SSI surveillance program should include standardized definitions of infection, effective surveillance methods and stratification of the SSI rates according to risk factors associated with the development of SSI. For many years wound contamination class was the only factor that was well described for predicting the risk for SSI. During the Study on the Efficacy of Nosocomial Infection Control (SENIC) Project, an index was developed that provided a better assessment of the risk of SSIs than had the traditional wound classification system. In 1991, a modification of the SENIC risk index by Culver et al. led to the National Nosocomial Infections Surveillance (NNIS) System risk index. This review examines the best surveillance method for surgical site infection.
Keywords: National Nosocomial infection surveillance; Nosocomial infection; Study of the Efficacy of Nosocomial Infection Control (SENIC) Score; Surgical site infection; Wound classification system